First Data of the Ichthyological Fauna in the Bandama River at the Lamto Scientific Nature Reserve (Côte d'Ivoire, West Africa) - Adou Yedehi Euphrasie; Blahoua Kassi Georges; Yeo Kolo; Konate Souleymane; Tiho Seydou (European Scientific Journal, ESJ, 2023)
Fish species composition and organization of the Bandama River at the scientific nature reserve of Lamto have been investigated for the first time. The study was conducted from March 2021 to February 2022. Gillnets and traps were used to collect fish. A total of 41 species belonging to 35 genera, 13 families, and 5 orders were captured. The best-represented orders were the Siluriformes with 5 families and 11 species and the Perciformes with 3 families and 14 species of fish. The Cichlidae, Mormyridae, and Alestidae represented the best diversified family with 13, 5, and 5 species respectively.This study also showed a decrease in the average size of individuals of the main species retained, which could reflect overexploitation of the stocks. The Shannon index (2.21 bits/ind.) and equitability (0.58) values obtained reflect a more or less distribution of individuals by species. These results will make it possible to establish a database for the conservation of this fish population and its habitat.